Tooth -A Potential Graft Material for Periodontal Regeneration? - Devani, VR; Manohar, B.; Humagain, M; Shetty, N (Kathmandu University Medical Journal, 2020)
Use of tooth as a promising replacement substitute has been validated by various animal as well as human studies. Though widely used in GBR and Sinus grafting techniques, its use in periodontal intrabony defect is not documented. In the present case report, the tooth graft has been placed in periodontal intrabony defect. Post-operative CBCT after 26 weeks revealed homogeneous incorporation of tooth graft. Clinical parameters show bone fill. However; results with larger sample size could further validate the use of tooth graft in periodontal regeneration.